1999
DOI: 10.1046/j.1365-2141.1999.01751.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of platelet glycoproteins and platelet/endothelial cell antibodies in patients with thrombotic thrombocytopenic purpura

Abstract: Platelets and sera from 12 patients with thrombotic thrombocytopenic purpura (TTP) and 12 healthy normal control subjects were examined. As determined by quantitative flow cytometry, prior to plasma exchange therapy platelet surface glycoprotein (GP) Ib levels were similar in TTP patients and normal controls (mean 20 188 and 20 226 molecules/platelet, respectively). Platelets from patients with TTP did, however, have significantly reduced levels of GPIIb/IIIa prior to plasmapheresis (mean 36 348 v 52 505 molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
1
21
1
Order By: Relevance
“…The IgG, plasma or serum from three out of five acute TTP patients enhanced platelet deposition, suggesting the presence of an antibody, probably against VWF‐cleaving protease in these three patients. These findings were in accordance with previous reports, where an antibody against VWF‐cleaving protease was identified (Fessler, 1997; Wright et al , 1999). In contrast, no effect was observed following addition of the IgG fraction of two other patients.…”
Section: Discussionsupporting
confidence: 94%
“…The IgG, plasma or serum from three out of five acute TTP patients enhanced platelet deposition, suggesting the presence of an antibody, probably against VWF‐cleaving protease in these three patients. These findings were in accordance with previous reports, where an antibody against VWF‐cleaving protease was identified (Fessler, 1997; Wright et al , 1999). In contrast, no effect was observed following addition of the IgG fraction of two other patients.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have suggested that complement is activated during acute episodes of TTP with reduced levels of serum C3 or elevated platelet-bound C3 (16, 36-38), with the reservation that older studies did not apply ADAMTS13 diagnostics. A more recent study demonstrated high levels of C3a and sC5b-9 during the acute phase of TTP, normalizing at remission (15), although this study did not find a parallel decrease in serum C3.…”
Section: Discussionmentioning
confidence: 99%
“…No further platelet function testing was done. By flow cytometry [22][23][24], platelet GPIba was 2% of control levels (SZ2 antibody) and aIIbb3, 148% (P2 antibody), the latter reflecting the increased size of the platelets. GPIba or GPIbb were not detected by immunoblotting but membrane integrins were normally present.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%